PENGUASAAN KALIMAT BAHASA INDONESIA MURID PAUD DI KECAMATAN TAMALANREA KOTA MAKASSAR: KAJIAN TRANFORMASI GENERATIF - Mutahharah, Mutahharah (JURNAL ILMU BUDAYA, 2017)
This research aims (1) to analyze a single sentence of Indonesian Language mastery of Paud student in district Tamalanrea Makassar city and (2) analyze the compound sentence mastery Indonesian Language Paud students in district Tamalanrea city of Makassar. This descriptive study using Generative Transformation approach. . The results of this research show that the Paud students sentence consists of two types of sentences, i.e. a single compound sentence and sentence. Transformation of single sentences, among others, the transformation of addition, subtraction, the turn, and permutasian, the merger of the two processes of transformation, and the transformation process of the four. Compound sentences Paud studentss in district of Tamalanrea, i.e. the compound sentences and compound sentences koordinatif subordinatif. Koordinatif compound sentences based on the relationship of contradiction between clauses and additive compound sentences while subordinatif based on a relationship of causation, agricultural, suppositions, and advanced.